Shaping Identities, Shaping Futures: The Socio-Religious Impact of Digital Culture on Nigerian Youth - Tonbrapade Japheth; Ndidi Justice Gbule; Christopher Opara (Khazanah Journal of Religion and Technology, 2025)
In the digital age, social media platforms have revolutionized the way young people form and express their identities. This study examines the complex and multifaceted relationship between digital culture and youth identity formation in Nigeria, a country with a rapidly growing youth population and increasing social media penetration. Using a mixed-methods approach, this research explores how digital platforms shape and reshape youth identities, influencing their self-concept, relationships, and worldviews. The study draws on two theoretical frameworks: technological determinism and social learning theory, providing a rich understanding of the interplay between digital culture and youth identity. The findings of this study reveal a paradoxical impact of digital culture on youth identities in Nigeria. On the one hand, digital platforms offer opportunities for self-expression, activism, entrepreneurship, and innovation. On the other hand, they also pose significant risks, including the erosion of cultural and religious identity, social media pressure, cyber-bullying, and other negative consequences. This study contributes to the growing body of research on digital culture and youth identity, highlighting the need for a much clearer understanding of the complex relationships between digital media, identity formation, and socio-religious contexts. The findings of this study have implications for policymakers, educators, and parents seeking to navigate the challenges and opportunities of digital culture for young people in Nigeria.